Conservation skills for the 21st century judgement, method, and decision making - Caple, Chris 1958-; Williams, Emily 1969- (Routledge, 2023)
Conservation Skills for the 21st Century provides a much-needed update to the original "Conservation Skills" volume, presenting an overview of current issues facing conservators of historic and artistic works. Beginning with the basics--why the past is important, as well as an overview of the nature and history of conservation--the book allows the reader to develop a holistic appreciation of the subject. As with the first edition, this volume assists with the development of judgement in conservation students and young professionals. A selection of new case studies representing issues conservators are likely to face in the 21st century illustrates the crucial considerations when proposing and executing a conservation treatment. Incorporating recent developments and use of new technologies in conservation processes, the book also covers topics such as: conservation ethics; recording and documentation; investigating and cleaning objects; stabilisation and restoration; values, decision-making, and responsibilities; preventative conservation; approaches to the treatment of working and socially active objects; sustainability in conservation; and the conservator's role as advocate. With detailed case studies and written in a clear, accessible style, Conservation Skills for the 21st Century remains essential reading for student conservators and conservation professionals around the globe working across a wide range of conservation disciplines"--